MUSIK SEBAGAI PENDEKATAN PSIKOLOGI POSITIF PERSPEKTIF JALALUDDIN RUMI - ridwanda, Muhammad liza; Achmad Khudori Soleh (Jurnal Studi Islam, 2025)
Abstract: This study explores the concept of music as a spiritual symbol in Jalaluddin Rumi's thinking as an approach to improving psychological well-being. The focus of this study is to understand how Rumi views music as a means of uniting the soul with God, explaining the concept of inner peace that can be achieved through music, and examining the potential of musical elements in poetry as a form of positive psychology. This research uses a qualitative approach with literature study, analyzing Rumi's works such as Masnawi and Fihi Ma Fihi, as well as supporting literature that discusses the relationship between spirituality, music, and psychological well-being. The results of the study show that: 1) Music in Rumi's poetry serves as a metaphor for spiritual longing and a means of achieving higher spiritual awareness. 2) Peace of mind can be achieved through self-reflection, spiritual experiences, and closeness to God, with music as a bridge to inner peace. 3) Musical elements in Rumi's poetry have the potential to create positive emotions, self-acceptance, and the search for meaning in life, so that they can be integrated into art- and spirituality-based psychological therapy. Keywords: Spiritual Music, Jalaluddin Rumi, Positive Psychology, Inner Peace, Spiritual Therapy. Abstrak: Penelitian ini mengeksplorasi konsep musik sebagai simbol spiritual dalam pemikiran Jalaluddin Rumi sebagai pendekatan untuk meningkatkan kesejahteraan psikologis. Fokus penelitian ini adalah bagaimana Rumi memandang musik sebagai sarana penyatuan jiwa dengan Tuhan, menjelaskan konsep ketenangan batin yang dapat dicapai melalui musik, serta mengkaji potensi unsur musikal dalam puisi sebagai bentuk psikologi positif. Metode penelitian ini menggunakan pendekatan kualitatif dengan studi literatur, menganalisis karya-karya Rumi seperti Masnawi dan Fihi Ma Fihi, serta literatur pendukung yang membahas hubungan antara spiritualitas, musik, dan kesejahteraan psikologis. Hasil penelitian menunjukkan bahwa: 1) Musik dalam puisi Rumi berfungsi sebagai metafora kerinduan spiritual dan sarana mencapai kesadaran spiritual yang lebih tinggi. 2) Ketenangan jiwa dapat dicapai melalui refleksi diri, pengalaman spiritual, dan kedekatan dengan Tuhan, dengan musik sebagai jembatan menuju kedamaian batin. 3) Unsur musikal dalam puisi Rumi berpotensi menciptakan emosi positif, penerimaan diri, dan pencarian makna hidup, sehingga dapat diintegrasikan dalam terapi psikologis berbasis seni dan spiritualitas. Kata kunci: Musik Spiritual, Jalaluddin Rumi, Psikologi Positif, Ketenangan Batin, Terapi Spiritualitas.